(3GdBKGQ GdELJeGYjI dHQGeL GdEUdGM GdEbJUGOj (B/s - (3GdMUQj, WGQb aGQhbs ((3GdEScfOQjI(B: s (3GdecJHI GdYUQjI(B, s, 2008)
(3jVe HQGeL GdEUdGM GdEbJUGOj aj eUQ, BKGQ HQGeL GdEUdGM GdEbJUGOj aj eUQ, BKGQ HQGeL GdEUdGM GdEbJUGOj Ydi GdabQ hGdJaGhJ aj JhRjY GdONd THcGJ GdCeGf GdMOjKI aj eUQ hGdBKGQ GdELJeGYjI dHQGeL GdEUdGM GdEbJUGOjs
(3GdeQGLY U(B.476s
Keywords: (3GdEUdGM GdEbJUGOjs; (3GdJNWjW GdEbJUGOjs; (3eUQ(B- (3GdJNWjW GdEbJUGOjs